2019
DOI: 10.12928/telkomnika.v17i4.11955
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of wireless balloon network using adaptive position tracking technology for post disaster event

Abstract: Limited resources in post-disaster areas, one of which is a communication where coordination needed for aid distribution in disaster areas. Wireless balloon technology as a solution for use in post-disaster areas. Bandwidth limitations and high delay in communication systems on wireless balloons create limitations in aid coordination, especially mobile device tracking on BPBD volunteers or officers. This research develops an effective communication system at the wireless balloon to track personal device office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This research uses an experimental method in which the development of materials, media, and models are tested directly and immediately corrected if it is not as intended. The steps used in this study are shown in Figure 1 7Developing and designing steps (8) Designing and developing the system as a whole, (9) Revision of each step, (10) Evaluation and Retest [18][19]. Based on Figure 1, there are 10 stages so that the results of this study are in the form of prototypes that are directly tested and evaluated on all students who use this virtual laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This research uses an experimental method in which the development of materials, media, and models are tested directly and immediately corrected if it is not as intended. The steps used in this study are shown in Figure 1 7Developing and designing steps (8) Designing and developing the system as a whole, (9) Revision of each step, (10) Evaluation and Retest [18][19]. Based on Figure 1, there are 10 stages so that the results of this study are in the form of prototypes that are directly tested and evaluated on all students who use this virtual laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Expert test of materials, models, and media to get according to students' abilities in practicum. These test results are in the form of media, models, and valid materials for the practicum modules that will be used by students [18][19]. Virtual laboratories are tested in small groups for students who take electrical machinery courses.…”
Section: Figure 1 Model Of Web Learning Developmentmentioning
confidence: 99%
See 3 more Smart Citations